IDENTIFIKASI MISKONSEPSI MAHASISWA PENDIDIKAN BIOLOGI PADA MATERI GENETIKA MENGGUNAKAN CERTAINTY OF RESPONSE INDEKS (CRI) - Alonemarera, A.S. (Jurnal Biotek, 2020)
This study is a qualitative descriptive study that aims to identify the student misconceptions on genetic material. The research was conducted at Sembilanbelas November University Kolaka. The research subjects were 23 students of the biology education study program who programmed the genetics course. Research data were collected using the Certainty of Response Index(CRI) diagnostic test technique to determine the location of misconception and interviews to determine the causes of misconception. The results showed the percentage of students understanding the genetic material of those who did not know the concept, knew the concept and experienced misconception was 17%, 39%, and 44%, respectively. There were misconceptions on five genetic submissions where the highest occurred in the sub material structure of gene organization with a percentage of 54%. The causes of students experiencing misconceptions are a passive attitude to seek information (43,5%), abstract genetic material (26,1%), learning methods that prioritize memorization techniques (17,4%), the use of high school books as the main reading reference (8,7%), and inability to translate the contents of reading material appropriately (4,3%). The conclusion is students experience misconceptions in all genetic sub materials tested with the highest percentage occurring in the sub-material of the gene organization structure. The most cause of the misconception is the passive attitude of students. There might be a need for the students to be more actively involved in building understanding, including independence in searching for information.